3D printing - Jordan, John M. (MIT Press, 2019)
An accessible introduction to 3D printing that outlines the additive manufacturing process, industrial and household markets, and emerging uses. The use of 3D printing--digitally controlled additive manufacturing -- is growing rapidly. Consumer models of 3D printers allow people to fabricate small plastic objects, from cabinet knobs to wedding cake toppers. Industrial uses are becoming widespread, as businesses use the technology to fabricate prototypes, spare parts, custom-fitted prosthetics, and other plastic or metal items, often at lower cost and with greater efficiency than standard manufacturing. In this volume in the MIT Press Essential Knowledge series, John Jordan offers an accessible introduction to 3D printing, describing the printing process, industrial and household markets, and emerging uses. Jordan outlines the stages of 3D printing, from idea to software model to a printable file that slices the planned object into printable layers to the finished object itself. He describes additive technologies, consumer 3D printing in homes and schools, mass customization (which can create tens of millions of unique items), and industrial uses. Jordan explains that although 3D printers have not become the ubiquitous home appliance once predicted, they are making inroads into mass markets; and he discusses the business factors that may hinder industry adoption of 3D printing technologies. He considers the possible unintended consequences of 3D printing on jobs, as companies scramble to find employees with an uncommon skill set; on business models and supply chains, as manufacturing is decentralized; and on patent law, as machines can be programmed to copy protected property. Finally, Jordan looks at new and emerging uses, including bioprinting, building construction, and micromachines.- Resumé vydavatel
Keywords: trojrozměrný tisk; three-dimensional printing; elektronické knihy; monografie; electronic books; monographs